(untitled) (Prithvi Academic Journal, 2020)
Academic stress has many negative effects on the students, and support from different levels can prevent this. This cross-sectional survey study among 322 students of class 8 and 10 from 3 public schools in Pokhara, Nepal was conducted to identify the role of perceived social support (PSS) from different levels (family, friends, and others) on academic-stress of students. The schools and participants were selected through a multistage cluster sampling technique. To collect the data self-administered questionnaires were distributed to the participants in their respective classrooms by one of the researchers. The data were analyzed in SPSS 20 with descriptive and inferential statistics (chi-square test and odds ratio at 95% confidence interval) at <0.05 level of significance. Findings revealed that 34.4% of students had moderate to high levels of academic stress. Among different socio-demographic and background variables, factors such as age of the adolescents, mother’s education level, socioeconomic status of the family, parental marital-status with whom adolescents are staying, home environment, night sleep, abuse at home, the problem has not listened, and feeling of discrimination were significantly associated with academic stress. The study concluded that perceived social support from the family has a greater preventive role along with other background factors. Hence, combined efforts of family and school are essential, where the family plays the most important role. The study findings have important implications for parents, family, school teachers, health personnel, counselors, and others in preventing academic stress and achieving mental wellbeing for adolescent students.